2018
DOI: 10.1039/c8tc00788h
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of charge carriers with magnetic entropy for power factor enhancement in Mn doped Sn1.03Te for thermoelectric applications

Abstract: An approach for utilizing magnetism to try to enhance thermoelectric properties of Mn doped self-compensated Sn1.03Te in context of its dilute magnetic nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 46 publications
2
36
0
1
Order By: Relevance
“…18 Recently, we have also demonstrated that the effect of interaction between magnetic dopants and charge carriers to be an unique concept for enhancement of the carrier effective mass (m*) and TE performance of SnTe. 3 These results indicate that TE performance of SnTe can be improved with doping and it can emerge as an alternative to PbTe.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…18 Recently, we have also demonstrated that the effect of interaction between magnetic dopants and charge carriers to be an unique concept for enhancement of the carrier effective mass (m*) and TE performance of SnTe. 3 These results indicate that TE performance of SnTe can be improved with doping and it can emerge as an alternative to PbTe.…”
Section: Introductionmentioning
confidence: 89%
“…More details of preparation and characterization details were described in our earlier work. [3][4][5] High temperature S and σ measurements were performed on a bar shape (~ 3 mm x 2 mm x 10 mm) samples in a homemade setup, where S was measured by differential method with ΔT = 10 K and σ in conventional four probe geometry under high vacuum. Quantum design physical property measurements system was used for low temperature transport and Hall Effect measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3,4) We have proposed the use of magnetism to enhance the properties of thermoelectric materials. Magnetic ion doping has been demonstrated for various systems, such as CuGaTe 2 , (5) Bi 2 Te 3 , (6) and SnSe, (7) to be a possible route to increase the power factor. Such an increase is not automatic and occurs in cases where electrical carriers have strong coupling with doped magnetic moments, effectively modifying transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…This will be detrimental to mobility, but the overall increase in power factor has been realized. (5)(6)(7) Some good-performance thermoelectric compounds have also been recently discovered amongst magnetic semiconductors, where magnetic elements are the main constituents. (8)(9)(10)(11)(12)(13) Carrier-doped CuFeS 2 exhibits a large power factor at room temperature (RT), speculated to originate from strong magnetic interactions.…”
Section: Introductionmentioning
confidence: 99%